Full Waveform Inversion Beneath the Central Andes: Insight Into the Dehydration of the Nazca Slab and Delamination of the Back‐Arc Lithosphere. Issue 7 (26th June 2021) - Gao, Yajian; Tilmann, Frederik; van Herwaarden, Dirk‐Philip; Thrastarson, Solvi; Fichtner, Andreas; Heit, Benjamin; Yuan, Xiaohui; Schurr, Bernd
Abstract: We present a new seismic tomography model for the crust and upper mantle beneath the Central Andes based on multi‐scale full seismic waveform inversion, proceeding from long periods (40–80 s) over several steps down to 12–60 s. The spatial resolution and trade‐offs among parameters are estimated through the multi‐parameter point‐spread functions. P‐ and S‐wave velocity structures with spatial resolution of 30–40 km for the upper mantle and 20–25 km for the crust could be resolved in the central study region. In our study, the subducting Nazca slab is clearly imaged in the upper mantle, with dip‐angle variations from the north to the south. Bands of low velocities in the crust and mantle wedge indicate intense crustal partial melting and hydration of the mantle wedge beneath the frontal volcanic arc, respectively, and they are linked to the vigorous dehydration from the subducting Nazca plate and intermediate depth seismicity within the slab. These low‐velocity bands are interrupted at 19.8°–21°S, both in the crust and uppermost mantle, hinting at the lower extent of crustal partial melting and hydration of the mantle wedge. The variation of lithospheric high‐velocity anomalies below the back‐arc from north to south allows insight into the evolutionary foundering stages of the Central Andean margin. A high‐velocity layer beneath the southern Altiplano suggests underthrusting of the leading edge of the Brazilian Shield. In contrast, a steeply westward dipping high‐velocity block and low‐velocity lithospheric uppermost mantle beneath the southern Puna plateau hint at the ongoing lithospheric delamination. Key Points: Normal dip subduction of the Nazca plate beneath the Central Andes Dehydration of the subducted Nazca plate, hydration of the mantle wedge and partial melting of the continental crust Underthrusting of the Brazilian Shield beneath the southern Altiplano and delamination beneath the southern Puna